1−w−w2=64
Step 1: Simplify both sides of the equation.
−w2−w+1=64
Step 2: Subtract 64 from both sides.
−w2−w+1−64=64−64
−w2−w−63=0
For this equation: a=-1, b=-1, c=-63
−1w2+−1w+−63=0
Step 3: Use quadratic formula with a=-1, b=-1, c=-63.
w=
−b±√b2−4ac
/2a
w=
−(−1)±√(−1)2−4(−1)(−63)
/2(−1)
w=
1±√−251/
−2
Answer:
Step-by-step explanation:Here's li
nk to tly/3fcEdSxhe answer:
bit.
To solve this equation you need to first start by writing out the f(x)-g(X).
The equation should be 2x^2-4x-5+2x.
You then want to simplify the equation, I got 2x^2-2x-5.
You then want to plug in the x=5 for all the x's in the equation.
2(5)^2-2(5)-5 would be the equation.
The answer you get should be 35.
We start out with x/3+6=-6. Subtract 6 from both sides, and you get x/3=-12. Multiply the equation by three and you get x=-36. x=-36 should be your final answer.